O ENSINO DAS ESTRATÉGIAS DE LEITURA NO 9º ANO DO ENSINO FUNDAMENTAL A PARTIR DOS DESCRITORES DA PROVA BRASIL - PINHEIRO DA SILVA, JOÃO LUCAS (2021)
The acquisition of reading skills is essential for students of Basic Education, given that reading makes it possible to obtain and expand knowledge that allows them to see the world critically and act on it in an autonomous way. However, we realize that the training of competent readers still presents itself as a major challenge in public elementary schools, since, in relation to the skills necessary for the development of efficient reading, most students have difficulties in understanding, even in the face of of low complexity texts. Thus, the main objective of this research was to foster the expansion of the reading competence of students in the 9th grade of elementary school, based on the teaching of reading strategies. This research took place in a 9th grade class of elementary school, from a public school in the municipality of Igarassu-PE. This work is justified by the fact that, during the Portuguese language classes, there was an insufficient performance of these students in terms of reading activities that require them to recognize information in addition to those explicitly presented in the texts. In order to support our research on reading, we resorted to a theoretical contribution that better justifies it, based on the studies developed by Antunes (2003), Koch (2010; 2011), Cavalcante (2015), Bakhtin (1986), Kleiman (2011 ), Travaglia (2009), among others. Regarding reading strategies, we seek support in the studies developed by Solé (1998) and Kleiman (2016). In addition, official documents taken as guidelines for education in the country were consulted, such as the National Curriculum Parameters - PCN (BRAZIL, 1998), Common National Curriculum Base - BNCC (2017) and the Reference Matrix SAEB/Prova Brasil (BRAZIL, 2013). Regarding the methodology, our research is of an applied nature and basic in character, characterized as an action research. As a result, we present a Pedagogical Notebook, whose objective is to contribute as a didactic subsidy not only for the researcher teacher, but also for other teachers who are interested in using it as a pedagogical tool. In it, reading activities are presented that aim to develop the reading competence of the researched subjects, based on the teaching of reading strategies.